2022
DOI: 10.1002/aocs.12588
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nanoencapsulation of Heracleum lasiopetalum by response surface methodology

Abstract: This study was carried out to optimize formulation for Heracleum lasiopetalum (golpar) extract nanoencapsulation by response surface methodology (RSM). The primary water-in-oil emulsion was fabricated by (5%-10%) golpar extract (GE), (40%-35%) emulsifier span 80 (EM), and (50%-60%) sunflower oil (SO). The coating materials were the mixture of Lepidium sativum seed gum (LSG) and whey protein concentrate (WPC) at different ratios (1:0, 1:1, and 0:1). The yield of nanoencapsulation of GE, particle size, and zeta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Heracleum lasiopetalum (Golpar-e barfi), a plant belonging to the Umbrella family, is found in the humid mountainous areas of Iran, Turkey, and Iraq. In Iranian traditional healing practices, Heracleum lasiopetalum serves various purposes, including its role as an antiseptic, spice, carminative, aid to digestion, flavor enhancer, and food supplement (14). Additionally, several studies have reported the anti-Candida, antibacterial, and antioxidant effects of Heracleum lasiopetalum (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Heracleum lasiopetalum (Golpar-e barfi), a plant belonging to the Umbrella family, is found in the humid mountainous areas of Iran, Turkey, and Iraq. In Iranian traditional healing practices, Heracleum lasiopetalum serves various purposes, including its role as an antiseptic, spice, carminative, aid to digestion, flavor enhancer, and food supplement (14). Additionally, several studies have reported the anti-Candida, antibacterial, and antioxidant effects of Heracleum lasiopetalum (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%